Application of Next-Generation Sequencing in Rapid Identification of Hospital-Acquired Infections: A Review and Analysis of Diagnostic Utility - Abuong, Fahad Sami; Fallatah, Majed Hashem; Aljuhani, Maryam Awad; Alhirbish, Hanan ahmed; terkustani, wejdan mohammed; Alahmadi, Nouf Oqla; Shamlan, Sara Ali; Aqeeli, Amal Mohammed; Rasheed, Sarah Ayman; alneami, Mashael Mohammed; et al. (Journal of Posthumanism, 2024)
Background: Nosocomial infections enhance morbidity and mortality so increasing health burdens .involves identifying the pathogen with its AMR profile and effective intervention is important as rapidly as possible. As conventional microbiological methods are most of them suffer from their slow speed and indispensable in this respect . Next-generation sequencing technologies represent powerful, culture-independent means for comprehensive diagnosis of HAIs. Objectives: This review aims to summarize the available evidence relating to the role of Next Generation Sequencing in the rapid identification and characterization of HAIs regarding diagnostic performance, the influence of such techniques on turnaround times, and utility relating to outbreak investigation and resistance prediction. Methods: A literature review was performed for the period from 2015 through 2024 for studies using WGS and mNGS in the diagnosis of HAIs. Data were synthesized to provide information on the identification of the pathogen, detection of AMR genes, TAT, and resolution of the outbreak. Results: NGS has increased discriminatory power compared to the standard methods. WGS reduces the time of outbreak resolution from weeks to days, with one manuscript resolving a K. pneumoniae outbreak in 5 days compared to 3 weeks using PFGE. mNGS directly on clinical samples has been able to disclose pathogens in culture-negative meningitis and pneumonia, where additive diagnostic yields of 30-40% have been described. WGS-based AMR prediction gave >95% concordance with phenotypic susceptibility for major Gram-negative pathogens.